(3TQM GdCNHGQ aj aVGFd GdfHj GdeNJGQ hBdg GdeUWajf GdCNjGQ ef GdCFeI GdCWgGQ Ydjge GdSdGes - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , hHg CJhcd hCSJYjf hUdhGJg Ydi eMeO GdCejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B91 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs